Flip Bucket Energy Damping Model Test on Karalloe Dam Spillway - Nabilah Shahnaz; Farouk Maricar; Bambang Bakri (International Association of Lowland Technology, 2022)
The Karalloe Dam was built with the aim of supplying raw water, for flood control and as a tourist attraction. This dam is also a dam with a type of rock embankment with a concrete membrane (Concrete Face Rockfill Dam) which has a side spillway without a door with the Mercu model of the Mercu Ogee type. The purpose of the study was to determine the level of effectiveness of energy absorbers with variations in flood discharge that had been determined using the Flip Bucket type. The research was conducted at the Natural Hydraulics Laboratory, Department of Civil Engineering, Hasanuddin University. This type of research is experimental with a physical hydraulic model test using primary data which includes building design data. The results showed that the calculation and testing on the physical model of the spillway building with a scale of 1:50 and a simulation with a numerical model obtained the results of the length of the jump the greater the discharge, the greater the length of the jump that occurred. At the 10th return period is 37.66 cm and the QPMF return period is 73.84 cm and in model testing the effectiveness of the energy damper is obtained which shows a reduction in the average velocity from the Launcher channel to the energy absorber each period, namely Q10th 44.75%, Q20th 37.79%, Q50th 35.09% , Q100th 32.87%, Q1000th 30.84% and QPMF 34.28%.